Experimental and Numerical Analyses of the Rational Loading Waveform in SHPB Test for Rock Materials. (3rd December 2018) - Luo, Song; Gong, Fengqiang
Abstract : Aiming at the determination of the rational loading waveform for rock materials, the comparative impact tests under the loadings of rectangular and half-sine stress waves were performed on red sandstone using an Ø50 mm SHPB apparatus. Experimental results with the rectangular stress wave affirm that the waveform dispersion and stress-strain curve oscillation frequently exist during the test of rock materials, which signifies that the accuracy of test results derived from the rectangular stress wave loading cannot be guaranteed. Under the loading of the half-sine stress wave, the phenomenon of wave dispersion during the tests has been eliminated radically, and there is no oscillation in the stress-strain curves. To further demonstrate the rationality of the half-sine wave loading in the SHPB test, by utilizing the three-dimensional numerical simulation approach, the propagations of rectangular, triangular, and half-sine stress waves travelling in the axial and radial directions of the SHPB with four elastic bar diameter sizes are analyzed and compared. The results show that the waveform dispersion of the rectangular and triangular stress waves always exists and will be more and more serious with increasing diameter size and propagation distance. For the half-sine stress wave, the waveform dispersion effect is very weak and not affected by the bar diameter size and propagation distance. The half-sine stress wave is the rational loading waveform for rock SHPB tests with different bar diameters.